Comparison of refractive outcomes in post cataract surgery using measurements from immersion and contact A-scan biometry techniques - Bariah Mohd-Ali,; Nazirin Arsad,; Zainora Mohammed, (penerbit ukm, 2012)
It is possible that different techniques used to measure axial length (AL) and anterior chamber depth (ACD) is the cause of discrepancy in refractive outcomes of cataract surgery. This study evaluated the agreement and repeatability of AL and ACD measurements using immersion and contact A-scan biometry techniques and compared the refractive outcomes from both techniques. Twenty four patients were evaluated for agreement and repeatability of AL and ACD measurements using the two different methods. The results were analyzed using Bland and Altman plots. Another 60 patients with age-related cataract were selected to compare the refractive outcomes between both methods. The IOL power was calculated using Sanders- Retzlaff- Kraff- Theoretical (SRK-T) equation. Refraction was determined between four to six weeks postoperatively and the results were analyzed using paired t-test. The results of this study showed good agreement between both techniques was noted with no significant difference detected between measurements (p > 0.05). Significant correlation was found in all parameters (AL: r = 0.99; p < 0.01, r = 0.99; p < 0.01) ACD: r = 0.91; p < 0.01, r = 0.97; p < 0.01). No significant difference in refractive outcomes of post cataract surgery was detected between the two techniques (p = 0.07). This study concludes that contact A-scan biometry and immersion techniques provide reliable results and should not be the cause of discrepancy in the refractive planned and outcome of cataract surgery.